On the Basic Principles of the Code of Execution and Security - Keča, Ranko (Zbornik radova Pravnog fakulteta u Novom Sadu, 2012)
The review of basic principles contained in Code of Execution and Security shows that in the great amount of solutions there is no major difference in comparison with earlier legislative. In general said refers to the principle of party control over the scope and nature of the proceedings, the right to be heard, principles of proceedings in written, publicity and indirectness and the principle of chronological order. More substantial differences are articulated in determination of procedural position of the parties, and indeed that the position of creditor is stronger supported. As a major change in that sense the right of the creditor to demand execution on all assets of debtor should be stressed out, as well as right of the creditor to demand on the very beginning of the executions procedure that debtor provides statement on his assets. At last, Code of Execution and Security introduces a possibility of execution been delegated to bailiff, what is completely new in Serbian law. Side by side with strengthening of the creditor’s position almost all procedural institutions of new execution legislative are expressing the idea of more effective and more efficient realization of this type of legal protection.